2016
DOI: 10.1159/000447829
|View full text |Cite
|
Sign up to set email alerts
|

Primary Tumour Resection Could Improve the Survival of Unresectable Metastatic Colorectal Cancer Patients Receiving Bevacizumab-Containing Chemotherapy

Abstract: Background: The effect of primary tumour resection (PTR) among metastatic colorectal cancer (mCRC) patients remains controversial. Combination chemotherapy with bevacizumab could improve the clinical outcomes of these patients, which might change the importance of PTR in the multi-disciplinary treatment pattern. Methods: We performed a non-randomized prospective controlled study of mCRC pts whose performance status (PS) scored ≤2 and who received bevacizumab combination chemotherapy (FOLFOX/XELOX/FOLFIRI) as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 27 publications
1
27
0
1
Order By: Relevance
“…All 17 studies evaluated OS [ 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 ], whereas only two evaluated PFS [ 24 35 ]. Three studies examined patients with colon cancer exclusively [ 28 32 38 ], one examined patients with rectal cancer exclusively [ 25 ], and 13 examined patients with colorectal cancer [ 23 24 26 27 29 30 31 33 34 35 36 37 39 ]; in 3 of the latter studies, data on patients with colon cancer could be separated from data on patients with rectal cancer [ 34 37 39 ]. Thirteen studies evaluated patients who received targeted chemotherapy [ 23 24 26 27 28 29 30 31 32 33 34 35 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…All 17 studies evaluated OS [ 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 ], whereas only two evaluated PFS [ 24 35 ]. Three studies examined patients with colon cancer exclusively [ 28 32 38 ], one examined patients with rectal cancer exclusively [ 25 ], and 13 examined patients with colorectal cancer [ 23 24 26 27 29 30 31 33 34 35 36 37 39 ]; in 3 of the latter studies, data on patients with colon cancer could be separated from data on patients with rectal cancer [ 34 37 39 ]. Thirteen studies evaluated patients who received targeted chemotherapy [ 23 24 26 27 28 29 30 31 32 33 34 35 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, Chinese colorectal cancer patients who are initially diagnosed as metastatic diseases are more willing to have a non-radical resection rather than receive palliative systemic chemotherapy until disease progression, which gave us a favorable opportunity to launch this retrospective observational cohort study [35]. In our center, the decision of receiving PTR treatment was made according to patients' intention, surgeons' assessment of surgery treatment risk as well as some other patients' condition and clinical features, such as abdominal pain, bloating and other mild symptoms which suggested probable aggravation.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of CRC has been a global health issue over the past decade [29, 30]. Studies have suggested that a high prevalence of mortality, recurrence and metastasis of CRC is associated with immunocompromised patients.…”
Section: Discussionmentioning
confidence: 99%